ANALISIS PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, HARGA DAN LOKASI MELALUI KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN CV. WANIA JAYA - Novita Ria Sundari; Yusril Kurniawan; Stepanus Sandy (CV. Adiba Aisha Amira, 2025)
This study aims to determine the effect of service quality, product quality, price and location through customer satisfaction on customer loyalty. The data collected in the study are qualitative data and quantitative data sourced from the workshop entrepreneur CV. Wania Jaya. This type of research is quantitative with a sample size of 60 and the method used to analyze is SEM with the Smart-PLS Version 4.0 analysis tool. The results of the analysis show that service quality does not affect customer satisfaction, product quality does not affect customer satisfaction, price does not affect customer satisfaction, location has a significant effect on customer satisfaction, service quality does not affect customer loyalty, product quality has a significant effect on customer loyalty, price does not affect customer loyalty, location does not affect customer loyalty, customer satisfaction does not affect customer loyalty, service quality does not affect customer loyalty through customer satisfaction, product quality does not affect customer loyalty through customer satisfaction, price does not affect customer loyalty through satisfaction, and location does not affect customer loyalty through customer satisfaction.